Long-term incidence of microvascular disease after bariatric surgery or usual care in patients with obesity, stratified by baseline glycaemic status: a post-hoc analysis of participants from the Swedish Obese Subjects study. Issue 4 (April 2017) - Carlsson, Lena M S; Sjöholm, Kajsa; Karlsson, Cecilia; Jacobson, Peter; Andersson-Assarsson, Johanna C; Svensson, Per-Arne; Larsson, Ingrid; Hjorth, Stephan; Neovius, Martin; Taube, Magdalena; Carlsson, Björn; Peltonen, Markku
Summary: Background: Bariatric surgery is associated with remission of diabetes and prevention of diabetic complications in patients with obesity and type 2 diabetes. Long-term effects of bariatric surgery on microvascular complications in patients with prediabetes are unknown. The aim of this study was to examine the effects of bariatric surgery on incidence of microvascular complications in patients with obesity stratified by baseline glycaemic status. Methods: Patients were recruited to the Swedish Obese Subjects (SOS) study between Sept 1, 1987, and Jan 31, 2001. Inclusion criteria were age 37–60 years and BMI of 34 kg/m 2 or greater in men and 38 kg/m 2 or greater in women. Exclusion criteria were identical in surgery and control groups and designed to exclude patients not suitable for surgery. The surgery group (n=2010) underwent gastric bypass (265 [13%]), gastric banding (376 [19%]), or vertical-banded gastroplasty (1369 [68%]). Participants in the control group (n=2037) received usual care. Bodyweight was measured and questionnaires were completed at baseline and at 0·5 years, 1 year, 2 years, 3 years, 4 years, 6 years, 8 years, 10 years, 15 years, and 20 years. Biochemical variables were measured at baseline and at 2 years, 10 years, and 15 years. We categorised participants into subgroups on the basis of baseline glycaemic status (normal [fasting blood glucose concentration <5·0 mmol/L], prediabetes [5·0–6·0 mmol/L], screen-detected diabetes [≥6·1 mmol/L at baseline visit without previous diagnosis], and established diabetes [diagnosis of diabetes before study inclusion]). We obtained data about first incidence of microvascular disease from nationwide registers and about diabetes incidence at study visits at 2 years, 10 years, and 15 years. We did the main analysis by intention to treat, and subgroup analyses after stratification by baseline glycaemic status and by diabetes status at the 15 year follow-up. The SOS study is registered withClinicalTrials.gov, NCT01479452 . Findings: 4032 of the 4047 participants in the SOS study were included in this analysis. We excluded four patients with suspected type 1 diabetes, and 11 patients with unknown glycaemic status at baseline. At baseline, 2838 patients had normal blood glucose, 591 had prediabetes, 246 had screen-detected diabetes, and 357 had established diabetes. Median follow-up was 19 years (IQR 16–21). We identified 374 incident cases of microvascular disease in the control group and 224 in the surgery group (hazard ratio [HR] 0·56, 95% CI 0·48–0·66; p<0·0001). Interaction between baseline glycaemic status and effect of treatment on incidence of microvascular disease was significant (p=0·0003). Unadjusted HRs were lowest in the subgroup with prediabetes (0·18, 95% CI 0·11–0·30), followed by subgroups with screen-detected diabetes (0·39, 0·24–0·65), established diabetes (0·54, 0·40–0·72), and normoglycaemia (0·63, 0·48–0·81). Surgery was associated with reduced incidence of microvascular events in people with prediabetes regardless of whether they developed diabetes during follow-up. Interpretation: Bariatric surgery was associated with reduced risk of microvascular complications in all subgroups, but the greatest relative risk reduction was observed in patients with prediabetes at baseline. Our results suggest that prediabetes should be treated aggressively to prevent future microvascular events, and effective non-surgical treatments need to be developed for this purpose. Funding: US National Institutes of Health, Swedish Research Council, Sahlgrenska University Hospital Regional Agreement on Medical Education and Research, and Swedish Diabetes Foundation.